Kampanye Ide Khilafah: Studi Manajemen Dakwah Akun Facebook Buletin Dakwah Kaffah - Jamilah Jamilah; Muhammad Rafii (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2022)
This study sees the management of da'wah in the campaigning caliphate by Kaffah Da'wah Bulletin (BDK) on Facebook. By utilizing primary and secondary data, which were obtained from observation and documentation, the researcher attempted to collect relevant data. Data were analyzed by reduction techniques, data display, and data verification. It concludes that the planning of BDK da'wah on Facebook is to present certain topics and problems in Indonesia with the caliphate system. Social, political, cultural, religious, and educational issues cannot be separated from BDK's manipulation to attract public attention and strengthen the caliphate fighters. This community in carrying out da'wah utilizes the symbols of the Koranic verse about Islam kaffah at the top of writings. In addition, the implementation of da'wah is also carried out through various technological features and popular media; jpeg, mobile, pdf, podcast, audio reading, and WA group. The public's interest with the popular media availability has increased the reputation and supporters of BDK in campaigning for Islamic law and the establishment of an Islamic caliphate. Furthermore, the evaluation of BDK is by reposting all scatter bulletins, this shows the high public interest in the caliphate campaign seen in posts that were redistributed by BDK redistributed about 2500 netizens